2020
DOI: 10.1055/s-0040-1708838
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Patients' Acceptance of and Satisfaction with Cloud-Based Telehealth for Chronic Disease Management: A Case Study in the Workplace

Abstract: Objective Understanding patients' acceptance of and satisfaction with telehealth use is important for workplace health promotion. In this study, we used a questionnaire to measure patients' usage behavior and satisfaction with cloud-based telehealth services in the workplace. We empirically investigated the factors that influence patients' usage and satisfaction based on data collected from 101 participants. Methods As its main research framework, this study utilized a revised version of the technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…It is a streamlined scheduling model, which is prototyped for distributed programming and efficient data scheduling tasks, in information systems, to facilitate the characteristics of computer parallelism, and it is necessary to constitute a common model as if the use of multi-threaded, multi-process processing, cloud computing technology is an important basis for the development of cloud computing, so as to focus on efficient programming models, in the case of large-scale data programming [ 15 ]. The parallelism of processes is major when it comes to large-scale data programming, as it can demonstrate efficient scheduling capabilities and can handle huge-scale data sets.…”
Section: Analysis Of Remote Clinical Care Technologies For Cloud Computingmentioning
confidence: 99%
“…It is a streamlined scheduling model, which is prototyped for distributed programming and efficient data scheduling tasks, in information systems, to facilitate the characteristics of computer parallelism, and it is necessary to constitute a common model as if the use of multi-threaded, multi-process processing, cloud computing technology is an important basis for the development of cloud computing, so as to focus on efficient programming models, in the case of large-scale data programming [ 15 ]. The parallelism of processes is major when it comes to large-scale data programming, as it can demonstrate efficient scheduling capabilities and can handle huge-scale data sets.…”
Section: Analysis Of Remote Clinical Care Technologies For Cloud Computingmentioning
confidence: 99%
“…Yet, one recent comprehensive study showed that vendors vary significantly in the quality of their UCD practices, ranging from well-developed UCD processes to fundamental misconceptions of the UCD process [ 8 ]. Several studies included in this synthesis addressed the value of following a user- or human-centered design approach broadly, either conducting UCD or HCD in their own work or noting the importance of these approaches in health informatics design [ 2 , 7 8 9 10 11 12 13 14 15 16 17 ]. However, for the reasons above, readers of HF/E-focused health informatics manuscripts should be careful to interpret the authors’ use of the (often confused) terms HCD and UCD, and not assume their design process is of high quality.…”
Section: Resultsmentioning
confidence: 99%
“…These mobile apps focused on a variety of chronic diseases such as diabetes and hypertension [ 63 , 122 ], cardiovascular health [ 30 , 58 , 121 ], cancer care [ 58 , 127 ], mental health [ 13 , 23 , 25 , 57 , 110 ], seizure management [ 57 ], bladder monitoring [ 56 ], tuberculosis treatment [ 15 ], and parental education [ 40 , 41 ]. A small number of studies focused on telehealth [ 10 , 14 , 140 ] and personal health records or patient portals [ 38 , 109 , 141 ].…”
Section: Resultsmentioning
confidence: 99%
“…Zhou [ 43 ] found ease of use as a critical factor that influences elderly population's acceptance of telehealth in China. Su et al [ 45 ] concluded that perceived usefulness and perceived ease of use positively affect the intention to use telehealth for chronic disease management [ 45 ]. One of the barriers in the growth of the telehealth services has been their revenue model.…”
Section: Discussionmentioning
confidence: 99%